(untitled) (Educational Perspectives Magazine (REPED), 2023)
The present work describes critically the development of the formation of the educators of párvulos in Chile. Al the same time, its contenls celebrates of one element for a project of investigation ampler than it at the moment makes a group of educational of the University on the initial formation of professors. Therefore, it will contribute excellent information that it could be used for the decisión making with the improvement of the quality of the formation that at the moment receives this type of professionals. The alluded to historical description , considers four great stages considered excellent in the evolution experienced by the process of formation of the professional. To the interior of each one of there landmarks, some critical knots are identified, that could and that still could be uffecting the transformations experienced by the formation of this professional.